2023
DOI: 10.1093/cid/ciad074
|View full text |Cite
|
Sign up to set email alerts
|

Infection-Induced Immunity Is Associated With Protection Against Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Decreased Infectivity

Abstract: Background The impact of infection-induced immunity on SARS-CoV-2 transmission has not been well established. Here we estimate the effects of prior infection induced immunity in adults and children on SARS-CoV-2 transmission in households. Methods We conducted a household cohort study between March 2020-November 2022 in Managua, Nicaragua where when one household member tests positive for SARS-CoV-2, household members are clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 49 This was mirrored in a household transmission study showing upon breakthrough infection, incidences of onward transmission were equally as likely from individuals that were previously infected or not. 50 Taken together, these epidemiological findings indicate that mucosal responses seeded by prior infection can mediate durable protection against breakthrough infections but are unlikely to impede onward transmission upon acquisition of infection. Moreover, these findings provide a proxy to assess responses by mucosal vaccine candidates.…”
Section: Introductionmentioning
confidence: 83%
“… 49 This was mirrored in a household transmission study showing upon breakthrough infection, incidences of onward transmission were equally as likely from individuals that were previously infected or not. 50 Taken together, these epidemiological findings indicate that mucosal responses seeded by prior infection can mediate durable protection against breakthrough infections but are unlikely to impede onward transmission upon acquisition of infection. Moreover, these findings provide a proxy to assess responses by mucosal vaccine candidates.…”
Section: Introductionmentioning
confidence: 83%
“…A household cohort study conducted in Managua, Nicaragua from March 2020 to November 2022 found that prior infection was associated with decreased infectivity in adults and adolescents. The secondary attack risk was 12.3 (95% CI: 10.3−14.8) for those with prior infection compared to 17.5 (95% CI: 14.8−20.7) for naive individuals 44 . Additionally, participants with prior infection were half as likely to be infected compared to those who were naive (RR 0.52, 95% CI: 0.38−0.70) 44 …”
Section: The Risk Of Transmission To Others After Reinfectionmentioning
confidence: 99%
“…The secondary attack risk was 12.3 (95% CI: 10.3−14.8) for those with prior infection compared to 17.5 (95% CI: 14.8−20.7) for naive individuals. 44 Additionally, participants with prior infection were half as likely to be infected compared to those who were naive (RR 0.52, 95% CI: 0.38−0.70). 44 The reduced infectivity in reinfection may be due to antibodies neutralizing a portion of the virus during the second infection.…”
Section: The Risk Of Transmission To Others After Reinfectionmentioning
confidence: 99%
See 2 more Smart Citations